To Determine the Frequency of Homocysteinemia in Patient with Acute Coronary Syndrome (Medical Forum Monthly, 2024)
Objective: To determine the frequency and factors associated with the ACS patients with homocysteinemia.Study Design: Cross-sectional study designPlace and Duration of Study: This study was conducted at the Department of Cardiology, Liaquat National Hospital & Medical College, Karachi from 1st August 2018 to 31st January 2019.Methods: All patient of age < 45 years presenting with chest pain were enrolled in the study. The patients were classified on the basis of ACS i.e. unstable angina, STEMI and NSTEMI. After confirming the diagnosis of ACS, homocysteine levels were assessed to confirm the diagnosis of elevated level of homocysteine (> 15µmol/l). Statistical analysis was done in SPSS version 26.Results: In this study, 107 patients with acute coronary syndrome were included for the analysis patient 40.11+2.59 years. The mean age of patient was 40.11+2.59 years. Male preponderance was observed in our study. The most common type of ACS was unstable angina 54 (50.5%) followed by NSTEMI and STEMI. However, the frequency of homocysteinemia among patient with acute coronary syndrome was 26.2%.Conclusion: In conclusion frequency of homocysyteinemia was 26.2%, common in males of particularly 31-44 years age group.